Does phosphate treatment for prevention of eutrophication pass the benefit-cost test? - Ian Bateman; Brett Day; Diane Dupont; Stavros Georgiou; Nuno Matias; Sanae Moritomo; Logakanthi Subramanian (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2006)
Over the past few decades the problem of eutrophication of water bodies has accelerated due to large additions of nutrients from human sources. This paper conducts a contingent valuation of household willingness to pay to reduce eutrophication impacts. The application employs the recently proposed one-and-one-half-bound dichotomous choice method for eliciting willingness to pay responses. It is also novel in that an examination of the rate and determinants of survey participation are analysed allowing superior aggregation of total values by allowing for those who refuse to be interviewed. A simple cost benefit analysis of anti-pollution measures is also reported.
Keywords: 330; aggregation; Contingent valuation; cost benefit analysis; determinants of survey participation; eutrophication; one-and-one-half-bound dichotomous choice method; pollution; willingness to pay